Transformasi Regulasi Pesantren dan Madrasah Diniyyah dalam Kerangka Negara Hukum Pancasila - Zhilal Afkari; Ahmad Muhammad Mustain Nasoha; Muhammad Nur Alvian Awwalus Sholeh; Izzuddin Ahmad Anugrah; Fadhil Muhammad Nadzif (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Islamic boarding schools and madrassas play an important role in the formation of religious character and education in Indonesia. The transformation of the regulations of these two institutions is crucial to adjust educational practices to the principles of the state of law of Pancasila. This study aims to analyze the dynamics of the regulation of Islamic boarding schools and madrasah diniyyah and its impact on the internalization of Pancasila values. The method used is qualitative descriptive through the study of documents, including laws and regulations and related literature. The results of the study show that there are significant changes, such as formal recognition of institutional status, curriculum standards, and accreditation mechanisms, which strengthen operational legality and the application of Pancasila values. In addition, the latest regulations also encourage the improvement of the quality of governance, transparency of institutional management, and strengthening the role of the community in the education process. The implementation of these regulations also provides space for learning innovation, integration of religious moderation, and adaptation to social development. In conclusion, the harmonization of these regulations allows for religious education that is relevant to the national context while maintaining religious identity. This research provides the basis for the development of a balanced Islamic education policy between state authorities, the needs of students, and the autonomy of educational institutions in the face of modern challenges and increasingly complex social changes.